Non-coated polyester base cloth for airbag
Patent Information
- Application Number
- CN202180071579.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-29
- Filing Date
- 2021-10-19
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2041-10-19
AI Technical Summary
Existing airbag base fabrics are mainly made of expensive nylon 6,6 fibers, and polyester fibers are prone to deterioration in humid and hot environments, making it difficult to maintain high mechanical properties and thermal stability after aging. There is no research on uncoated polyester base fabrics with excellent hydrolysis resistance.
Using aluminum compounds and phosphorus compounds or phenolic compounds as catalysts, the acid value increase rate of polyester fibers is controlled to be below 150%, and the solvent extraction rate is ≤0.1%. Through high-temperature hot water bath and high vacuum suction treatment, the performance of the base fabric is ensured to be maintained after 24 hours at 121℃ and 100%RH, meeting the flammability test standards.
This technology enables polyester fiber base fabric to maintain high mechanical properties and thermal stability after aging, meets flammability test standards, and reduces production costs.
Smart Images

Figure BDA0004186623740000111
Abstract
Description
Technical Field
[0001] This invention relates to polyester fabric for airbags. More specifically, this invention relates to polyester fabric for airbags that maintains a high level of mechanical properties as an airbag fabric even after aging. Background Technology
[0002] Airbags are widely installed in automobiles as safety protection devices for occupants, and are installed in various locations, such as airbags for driver's and front passenger seats, thigh protection airbags integrated into passenger seats, and curtain airbags that deploy along the side windows. The amount of airbag base fabric used in each vehicle is increasing daily. Currently, the base fabric used in airbags is mainly formed from polyamide fibers, particularly nylon 6,6 fibers, which have properties suitable for airbag base fabrics. However, nylon 6,6 fibers are relatively expensive, and costs increase with the wider use of airbags. Therefore, there is a need for base fabrics made from polyester fibers, whose raw yarn cost is lower than that of nylon 6,6 fibers.
[0003] The base fabric for airbags must maintain sufficient performance in accelerated aging and degradation tests assuming the operating environment. Although polyester fibers have been found to degrade easily in humid and hot environments, to meet this requirement, for example, Patent Document 1 suggests polyester fibers targeted for use with catalysts other than antimony compounds.
[0004] However, such fibers have a slightly poor thermal stability. These fibers have been provided for industrial materials, such as membranes; however, they have not yet been provided for use in airbags involving human life. No research has been conducted on base fabrics for uncoated airbags; and no polyester uncoated base fabrics with excellent hydrolysis resistance have been substantially disclosed.
[0005] Citation List
[0006] Patent documents
[0007] Patent Document 1: JP2002-242043A Summary of the Invention
[0008] Technical issues
[0009] One object of the present invention is to provide a polyester fiber for airbags in a base fabric for airbags that maintains a high level of mechanical properties even after aging, and at the same time has thermal stability.
[0010] Solution to the problem
[0011] To achieve the aforementioned objective, the inventors conducted in-depth and meticulous research and completed this invention. Specifically, the invention is described below.
[0012] (1) A non-coated polyester base fabric for airbags, wherein the non-coated polyester base fabric for airbags meets the requirement that the acid value increase rate is less than 150% after being treated at 121°C and 100% relative humidity for 24 hours, and meets the standard for flammability testing of motor vehicle interior trim, namely the standard for flammability testing of FMVSS No. 302.
[0013] The increase in acid value (AR) after 24 hours of treatment at 121°C and 100% relative humidity is calculated using the following formula:
[0014] AR(%) = AE / AI × 100,
[0015] in
[0016] AE (eq / ton) represents the acid value of the uncoated polyester fabric for airbags obtained after treatment at 121°C and 100% relative humidity for 24 hours.
[0017] AI (eq / ton) represents the initial acid value of the uncoated polyester base fabric for airbags.
[0018] (2) A polyester base fabric for uncoated airbags, wherein the solvent extraction rate of the base fabric is less than 0.1%.
[0019] (3) A non-coated polyester base fabric for airbags, wherein the concentration of phosphorus catalyst is above 10 ppm.
[0020] (4) A non-coated polyester fabric for airbags, wherein the concentration of aluminum catalyst is above 5 ppm.
[0021] Beneficial effects of the invention
[0022] According to the present invention, even if the base fabric using relatively inexpensive polyester fibers changes over time when used in airbags, it can maintain a high level of performance, while also having excellent thermal stability and meeting flammability test standards. Detailed Implementation
[0023] The technical concept of this invention mainly includes the following elements. Specifically, the acid value increase rate after 24 hours of degradation treatment at 121°C and 100% relative humidity is less than 150%. The pressure at 121°C and 100% RH is 2 atm, which is the saturated vapor pressure.
[0024] The rate of increase in acid value (AR) after treatment at 121°C and 100% relative humidity for 24 hours is defined by the following formula.
[0025] AR(%) = AE / AI × 100
[0026] An oxidation increase rate of 100% (AR) indicates no oxidation change, while an oxidation increase rate of more than 100% indicates an increase in oxidation.
[0027] In this paper, AE (eq / ton) and AI (eq / ton) represent the acid value of the uncoated polyester fabric for airbags and the initial acid value of the uncoated polyester fabric for airbags obtained after treatment at 121°C and 100% relative humidity for 24 hours, respectively.
[0028] The inventors analyzed the polyester base fabric in detail and found that even when using a polyester base fabric, a polyester base fabric with an acid value increase rate of less than 150% after being treated at 121°C and 100% relative humidity for 24 hours can provide an airbag base fabric with aging degradation comparable to that of an airbag base fabric formed from polyamide fibers.
[0029] The increase in acid value after treatment at 121°C and 100% relative humidity for 24 hours is preferably below 140%. There is no particular limitation on the lower limit of the increase in acid value.
[0030] In contrast, the tensile strength retention rate of the base fabric after 3000 hours of treatment at 80°C and 95% relative humidity is one of the aging and deterioration treatment conditions for automobile manufacturers, and it is considered an important factor in indicating resistance to aging and deterioration.
[0031] The inventors conducted a detailed analysis of the polyester base fabric and discovered a strong correlation between the tensile strength retention rate after treatment at 80°C and 95% relative humidity for 3000 hours and the acid value increase rate after treatment at 121°C and 100% relative humidity for 24 hours. This confirmed that the acid value increase rate after treatment at 121°C and 100% relative humidity for 24 hours can be an important indicator of hydrolysis resistance.
[0032] In this invention, the tensile strength before treatment is taken as 100%, and the relative value of the tensile strength after treatment is defined as the tensile strength retention rate after treatment. The tensile strength retention rate after treatment at 80°C and 95% relative humidity for 3000 hours is preferably 80% or more, and more preferably 90% or more.
[0033] The treatment was carried out under the usual conditions for treating polyester films, at 121°C and 100% relative humidity for 24 hours. Compared with 3000 hours of treatment at 80°C and 95% relative humidity, the treatment under this condition significantly reduced the processing time.
[0034] In this invention, to achieve an acid value increase of less than 150% after treatment at 121°C and 100% relative humidity for 24 hours, the following elements are primarily required. Specifically, this means using polyester fibers employing catalysts other than common antimony compounds.
[0035] As cited in JP2002-242043A, catalysts other than antimony compounds are polyester polymerization catalysts composed of aluminum compounds and phosphorus compounds or phenolic compounds, particularly phosphorus compounds having a phenolic moiety in the same molecule. The use of this catalyst enables the suppression of foreign matter formation due to metal precipitation, which contributes to hydrolysis resistance.
[0036] Aluminum compounds with a catalyst concentration of 5 ppm or higher can exhibit catalytic effects. More preferably, the catalyst concentration of the aluminum compound is 10 ppm or higher. Excessively high catalyst concentrations of aluminum compounds may cause the generation of foreign matter; therefore, the catalyst concentration of the aluminum compound is preferably 25 ppm or lower.
[0037] Phosphorus compounds with a catalyst concentration of 10 ppm or higher can exhibit catalytic effects. A catalyst concentration of 20 ppm or higher is more preferable. Excessively high catalyst concentrations of phosphorus compounds may cause the generation of foreign matter; therefore, a catalyst concentration of 50 ppm or lower is preferably preferred.
[0038] However, compared to the thermal stability achieved by polyester fibers using antimony catalysts, the use of such catalysts results in slightly poorer thermal stability. Polyester fibers using these catalysts do not meet the flammability test standards for automotive interior trim, namely the FMVSS No. 302 flammability test.
[0039] The inventors have conducted in-depth and detailed research and discovered that reducing the amount of residual organic matter from spinning oils, i.e., lowering the solvent extraction rate, is a key factor in solving this problem. The solvent extraction rate of this invention is determined based on the mass of the extracted material obtained by the test method specified in ASTM D 2257-98, and is expressed as a ratio to the mass of the polyester base fabric before treatment.
[0040] In particular, when the rate of increase in acid value decreases, residual organic matter may remain, and the solvent extraction rate cannot be reduced using conventional methods. Therefore, it has long been considered difficult to simultaneously achieve both flammability and a reduction in the rate of increase in acid value.
[0041] The inventors have analyzed in detail polyester fabrics using polyester polymerization catalysts composed of aluminum compounds and phosphorus compounds or phenolic compounds, particularly phosphorus compounds having a phenolic structure in the same molecule, and discovered that when the solvent extraction rate of the polyester fabric is 0.1% or less, a polyester airbag fabric that meets the flammability test standard of FMVSS No. 302 (Federal Motor Vehicle Safety Standards No. 302) can be obtained. The solvent extraction rate is more preferably 0.05% or less. From the viewpoint of tear strength performance of the airbag fabric, the lower limit of the solvent extraction rate is preferably 0.01% or more.
[0042] As a strategy for achieving a solvent extraction rate of less than 0.1%, the inventors discovered two key elements: immersion in hot water at a temperature of 90°C or higher, and setting the vacuum pressure used for water extraction to 30 kPa or higher. While hot water baths have traditionally been used for the shrinkage processing of airbag base fabrics, the hot water bath temperature and vacuum pressure were not determined for the purpose of controlling the solvent extraction rate. The current detailed study found that by treating the water at a high hot water bath temperature followed by extraction of the solvent-containing water under high vacuum pressure, the solvent extraction rate can be effectively reduced.
[0043] The temperature of the hot water bath during the processing of the base fabric, specifically the temperature of the hot water, is preferably 90°C or higher, more preferably 95°C or higher, and even more preferably 98°C or higher. Hot water at a temperature of 90°C or higher can reduce fatty acid esters, which are the main residual components, thereby reducing the solvent extraction rate of the polyester base fabric. The upper limit of the hot water bath temperature is 100°C, which is the boiling point of water.
[0044] The inventors conducted in-depth and detailed research and found that if the vacuum pressure after the hot water bath during base fabric processing is 30 kPa or higher, the solvent content in the fibers can be reduced, which allows for a decrease in the solvent extraction rate of the polyester base fabric. A vacuum pressure of 35 kPa or higher is more preferable. From the viewpoint of spinnability during base fabric processing, an upper limit of 45 kPa or lower is preferably preferred.
[0045] The polyester base fabric for airbags according to the invention is preferably formed from polyester fibers with a total fineness of 200 to 555 dtex. Although polyester fibers tend to have reduced packing capacity due to their greater stiffness than nylon 6,6 fibers, polyester fibers with a total fineness of 200 dtex or more do not require excessively high weave density, thus limiting excessive increase in the bonding force between warp and weft yarns, making it easier for the packing capacity in the airbag module to fall within an appropriate range. Polyester fibers with a total fineness of less than 555 dtex also make it easier to limit excessive increase in the stiffness of the yarns constituting the fabric.
[0046] The polyester base fabric for airbags according to the present invention is preferably formed from polyester fibers with a monofilament fineness of 6.0 dtex or less. Polyester fibers with a monofilament fineness of 6.0 dtex or less can achieve both spinnability and airbag containment.
[0047] Examples of polyester fibers used in the polyester base fabric for airbags according to the invention include polyethylene terephthalate and polybutylene terephthalate; the polyester fibers may be fibers composed of copolyesters formed by copolymerizing polyethylene terephthalate or polybutylene terephthalate with an aliphatic dicarboxylic acid (such as isophthalic acid, sodium 5-sulfoisophthalate or adipic acid) as an acid component.
[0048] The polyester base fabric for airbags according to the present invention preferably has a weave density of 40 threads / 2.54 cm or more in both the warp and weft directions, and more preferably 46 threads / 2.54 cm or more. A weave density of 46 threads / 2.54 cm or more can limit the loss of the base fabric structure during the weaving process. Although there is no particular upper limit to the weave density, it is preferably 70 threads / 2.54 cm or less due to limitations on weft insertion during weaving.
[0049] In this invention, weaving density is measured according to JIS L1096 (2010) 8.6.1. Specifically, the sample is placed on a platform, and unnatural wrinkles, curls, and tension are removed. Then, the number of warp and weft yarns in each 2.54-cm segment in five different sections is counted, and the average value of each yarn per unit length is calculated and determined as the weaving density.
[0050] From a mechanical point of view, the tensile strength of the polyester base fabric for airbags according to the present invention is preferably 500 N / cm or more, and more preferably 550 N / cm or more. Although there is no particular limitation on the upper limit of tensile strength, it is preferably 1000 N / cm or less, and more preferably 900 N / cm or less, relative to the total fineness and tensile strength of the polyester multifilaments used, and the weaving density of the airbag base fabric.
[0051] In this invention, the tensile strength of the base fabric is measured according to JIS L1096(2010)8.14.1A (marking strip method). Specifically, the test sample is clamped in a tensile testing machine under initial load, and the test is performed at a tensile rate of 200 m / min with a test sample width of 50 mm and a clamping distance of 200 mm. The strength (N) of the sample when it is cut is then measured. However, samples that break within 10 mm of the clamping distance and samples that break abnormally are excluded.
[0052] The typical preparation method of the uncoated polyester fabric for airbags of the present invention is summarized below; however, the present invention is not limited to this method, as long as it can exhibit the same effect as the present invention.
[0053] This invention relates to a method for preparing a polyester base fabric for uncoated airbags, wherein polyester multifilament yarn spun from a polymer containing aluminum and phosphorus compounds is woven, the yarn is then passed through a hot water bath at a temperature of 90°C or higher, and subjected to vacuum pressure of 30 kPa or higher, followed by drying.
[0054] Preferably, the process involves continuously passing the material through a hot water bath at a temperature of 90°C or higher and performing suction at a pressure of 30 kPa. Furthermore, in the preparation method of this invention, a heat-setting process, represented by a tenter frame needle, can be added without any problems.
[0055] The uncoated polyester base fabric for airbags according to the invention can be used as a base fabric suitable for further coating on one or both sides because the polyester base fabric has excellent properties, such as heat resistance and mechanical strength that does not change over time. In such cases, elastomeric resins are preferred for coating resins; however, silicone resins are the most effective. The method for coating the resin can be a conventional known method. From the viewpoint of ease of adjusting the coating amount and the effect of mixing foreign matter (protrusions), coating by blade coating, especially by knife-on-air coating, is most preferred. For example, airbags formed from the uncoated polyester base fabric for airbags according to the invention, and airbags formed from coated polyester base fabric for airbags obtained by coating the aforementioned uncoated polyester base fabric for airbags, are suitable for driver airbags, front passenger airbags, curtain airbags, side airbags, knee airbags, seat airbags, and reinforcing fabrics. Because the uncoated polyester fabric for airbags according to the present invention, and the coated polyester fabric for airbags obtained by further adding a coating to the uncoated polyester fabric for airbags, have particularly high packability, such polyester fabrics can be preferably used for airbags that particularly require packability. For example, the fabric can be used for driver airbags, front passenger airbags, curtain airbags, side airbags, and knee airbags.
[0056] Example
[0057] The present invention has been described in more detail below with reference to embodiments. However, the present invention is not limited to the following embodiments, and modifications can certainly be made as appropriate, and the extent of such modifications is consistent with the objectives described above and below, all of which are included within the technical scope of the present invention. The various performance testing methods performed in the following embodiments are as follows.
[0058] Acid value of polyester base fabric
[0059] Accurately weigh 0.2 g of the sample (polyester fabric) that has been dried at 70°C for 16 hours. Add 10 ml of benzyl alcohol and the weighed sample to a test tube, and immerse the test tube in an oil bath heated to 205°C. Dissolve the sample using a magnetic stirrer while stirring with a glass rod for 5 minutes.
[0060] Titration was performed using a 0.04 mol / L potassium hydroxide solution (ethanol solution). Phenol red was used as an indicator, and the endpoint was set at the point where the color changed from yellow-green to pale red. The amount of carboxyl end groups of the esterification product was determined and expressed as eq / 1 ton of polyester base fabric.
[0061] Weave density of the base fabric
[0062] Measurements were performed according to JIS L1096(2010)8.6.1. The sample was placed on a platform, and unnatural wrinkles and tension were removed. The number of warp and weft yarns in each 2.54-cm segment in five different sections was counted, and the average value per unit length was calculated and determined as the density.
[0063] Tensile strength and elongation of the base fabric
[0064] Measurements were performed according to Method A (marking strip method) of JIS L 1096 (2010) 8.14.1. Each test sample, 50 mm wide, was clamped in a tensile testing machine under a first load and tested at a tensile rate of 200 m / min and a clamping distance of 200 mm until the sample broke. The strength (N) and elongation at break (mm) were then determined. However, samples that broke within 10 mm of the clamps or exhibited abnormal fractures were excluded.
[0065] Total fineness of raw yarn
[0066] Total fineness was measured according to JIS L1013 (2010) 8.3.1. More specifically, after obtaining a sample with a length accurate to 90 cm under initial load, its oven-dry mass was weighed, and the total fineness (dtex) was calculated according to the following formula (7). The average of five measurements was defined as the total fineness.
[0067] F0=1000 xm / 0.9 x + (100+R0) / 100 ··· (7)
[0068] F0: Corrected fineness (dtex)
[0069] L: Length of the sample (m)
[0070] m: the oven-dry mass of the sample (g),
[0071] R0: Official moisture content (official regain) (%).
[0072] Catalyst concentrations of aluminum and phosphorus
[0073] Metal concentration was determined by ICP emission spectroscopy. The measuring apparatus used was a SPECTRO BLUE TI (SPECTRO). The measurement conditions were as follows: plasma power: 1400 W, plasma gas flow rate: 12 L / min, nebulizer gas flow rate: 1.0 L / min, auxiliary gas flow rate: 1.0 L / min.
[0074] The quantitative conditions for aluminum and phosphorus are as follows. Yttrium nitrate solution was added to approximately 0.5 g of the sample for hydrolysis, and the residue was then dissolved in 1.2 N hydrochloric acid, thereby measuring the sample. The quantitative conditions for aluminum are as follows. After carbonization / incineration of approximately 0.5 g of the sample, the residue was dissolved in 1.2 N hydrochloric acid, thereby measuring the sample. The concentrations of aluminum and phosphorus (by weight) obtained through this measurement are considered the catalyst concentrations of aluminum and phosphorus in this invention.
[0075] Example 1
[0076] The warp and weft yarns used were 555 dtex / 144f polyester multifilament yarns (the cross-sectional surface of the monofilaments had a circular shape), spun from polymers containing aluminum and phosphorus compounds. Both warp and weft yarns were woven at a predetermined weave density of 51 yarns / 2.54 cm using a water-jet loom in a plain weave pattern. The base fabric was then subjected to a 98°C hot water shrinkage bath without drying, followed by vacuum pressure at 35 kPa, and then passed through a furnace at 160°C to obtain an uncoated base fabric. Table 1 shows the preparation conditions and the physical properties of the resulting uncoated base fabric.
[0077] In Table 1, treatment at 121°C and 100% relative humidity for 24 hours is defined as 121°C 100% RH 24H.
[0078] Example 2
[0079] The warp and weft yarns were made of polyester multifilament yarn with a fineness of 555 dtex / 144f (the cross-sectional surface of the monofilaments has a circular shape), spun from a polymer containing aluminum and phosphorus compounds. Both the warp and weft yarns were woven at a predetermined weave density of 51 yarns / 2.54 cm using a water-jet loom in a plain weave pattern. The base fabric was then subjected to a 98°C hot water shrinkage bath without drying, followed by vacuum pressure at 40 kPa, and then passed through a furnace at 160°C to obtain an uncoated base fabric. Table 1 shows the preparation conditions and the physical properties of the resulting uncoated base fabric.
[0080] Example 3
[0081] The warp and weft yarns were made of polyester multifilament yarn with a fineness of 555 dtex / 144f (the cross-sectional surface of the monofilament has a circular shape), spun from a polymer containing aluminum and phosphorus compounds. The yarns were woven in a plain weave pattern using a water-jet loom with a predetermined weave density of 51 yarns / 2.54 cm in both warp and weft. The base fabric was then subjected to a 90°C hot water shrinkage bath without drying, followed by vacuum pressure of 30 kPa, and then passed through a furnace at 160°C to obtain an uncoated base fabric. Table 1 shows the preparation conditions and the physical properties of the resulting uncoated base fabric.
[0082] Example 4
[0083] The warp and weft yarns were made of polyester multifilament yarn with a fineness of 470 dtex / 96f (the cross-sectional surface of the monofilaments has a circular shape), spun from a polymer containing aluminum and phosphorus compounds. Both the warp and weft yarns were woven at a predetermined weave density of 56 yarns / 2.54 cm using a water-jet loom in a plain weave pattern. The base fabric was then subjected to a 98°C hot water shrinkage bath without drying, followed by vacuum pressure at 35 kPa, and then passed through a furnace at 160°C to obtain an uncoated base fabric. Table 1 shows the preparation conditions and the physical properties of the resulting uncoated base fabric.
[0084] Comparative Example 1
[0085] The warp and weft yarns were made of polyester multifilament yarn with a fineness of 555 dtex / 144f (the cross-sectional surface of the monofilaments has a circular shape), spun from a polymer containing aluminum and phosphorus compounds. Both the warp and weft yarns were woven at a predetermined weave density of 51 yarns / 2.54 cm using a water-jet loom in a plain weave pattern. The base fabric was then subjected to a 50°C hot water shrinkage bath without drying, followed by vacuum pressure at 20 kPa, and then passed through a furnace at 160°C to obtain an uncoated base fabric. Table 1 shows the preparation conditions and the physical properties of the resulting uncoated base fabric.
[0086] Comparative Example 2
[0087] The warp and weft yarns were made of polyester multifilament yarn with a fineness of 555 dtex / 144f (the cross-sectional surface of the monofilaments has a circular shape), spun from a polymer containing antimony compounds. Both the warp and weft yarns were woven at a predetermined weave density of 51 yarns / 2.54 cm using a water-jet loom in a plain weave pattern. The base fabric was then subjected to a 50°C hot water shrinkage bath without drying, followed by vacuum pressure at 20 kPa, and then passed through a furnace at 160°C to obtain an uncoated base fabric. Table 1 shows the preparation conditions and the physical properties of the resulting uncoated base fabric.
[0088] Table 1
[0089]
[0090] Industrial applicability
[0091] This invention relates to a polyester base fabric for airbags that retains the mechanical properties of an airbag, exhibits high restraint performance in capturing occupants upon deployment, and maintains a high level of performance even after the base fabric undergoes changes over time. This invention will expand the use of relatively inexpensive polyester airbags, thus greatly contributing to the development of the industry.
Claims
1. A polyester base fabric for uncoated airbags, The polyester contains aluminum compounds and phosphorus compounds or phenolic compounds as catalysts. The solvent extraction rate of the base fabric is less than 0.1%, the acid value increase rate after treatment at 121°C and 100% relative humidity for 24 hours is less than 150%, and it meets the flammability test standard for automotive interior trim, namely the FMVSS No. 302 flammability test standard. The concentration of phosphorus catalyst is above 10 ppm, or the concentration of aluminum catalyst is above 5 ppm. in, The base fabric is obtained by a method comprising the following steps: immersing the base fabric in hot water at a temperature of 90°C or higher in a hot water bath, and then removing water under a vacuum pressure of 30 kPa or higher.
Citation Information
Patent Citations
Base fabric for non-coat air bag
JP1995090747A
High-strength polyester fiber fabric
JP2002242043A
